DkPK Genes Promote Natural Deastringency in C-PCNA Persimmon by Up-regulating DkPDC and DkADH Expression - Guan, Changfei; Du, Xiaoyun; Zhang, Qinglin; Ma, Fengwang; Luo, Zhengrong; Yang, Yong (Frontiers in Plant Science, 2017)
The astringency of Chinese pollination-constant non-astringent (C-PCNA) persimmon (Diospyros kaki Thunb.) can be naturally removed on the tree. This process is controlled by a single locus and is dominant against other types of persimmons; therefore, this variant is an important candidate for commercial cultivation and the breeding of PCNA cultivars. In our previous study, six full-length coding sequences (CDS) for pyruvate kinase genes (DkPK1-6) were isolated, and DkPK1 is thought to be involved in the natural deastringency of C-PCNA persimmon fruit. Here, we characterize the eight other DkPK genes (DkPK7-14) from C-PCNA persimmon fruit based on transcriptome data. The transcript changes in DkPK7-14 genes and correlations with the proanthocyanidin (PA) content were investigated during different fruit development stages in C-PCNA, J-PCNA and non-PCNA persimmon; DkPK7 and DkPK8 exhibited up-regulation patterns during the last developmental stage in C-PCNA persimmon that was negatively correlated with the decrease in soluble PAs. Phylogenetic analysis and subcellular localization analysis revealed that DkPK7 and DkPK8 are cytosolic proteins. Notably, DkPK7 and DkPK8 were ubiquitously expressed in various persimmon organs and abundantly up-regulated in seeds. Furthermore, transient over-expression of DkPK7 and DkPK8 in persimmon leaves led to a significant decrease in the content of soluble PAs but a significant increase in the expression levels of the pyruvate decarboxylase (DkPDC) and alcohol dehydrogenase genes (DkADH), which are closely related to acetaldehyde metabolism. The accumulated acetaldehyde that results from the up-regulation of the DkPDC and DkADH genes can combine with soluble PAs to form insoluble PAs, resulting in the removal of astringency from persimmon fruit. Thus, we suggest that both DkPK7 and DkPK8 are likely to be involved in natural deastringency via the up-regulation of DkPDC and DkADH expression during the last developmental stage in C-PCNA persimmon.